Evaluating near infrared spectroscopy as a rapid screening tool for microbiological safety of rooibos (Aspalathus linearis) - Smith, Anne (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScFoodSc)--Stellenbosch University, 2024.